Efficacy and Safety of Tirzepatide in the Treatment of Obesity in Adults: A Comprehensive Review - Karolina Skonieczna; Olimpia Wiciun; Kacper Ordon; Magdalena Badziąg; Paulina Szulc; Laura Kurczoba; Martyna Kłossowska; Olga Kądziołka (Quality in Sport)
Obesity is one of the most serious health challenges of the modern world, associated with an increasing incidence and serious health consequences, including cardiovascular diseases and type II diabetes. Pharmacotherapy of obesity is developing rapidly, and tirzepatide, an agonist of GIP and GLP-1 receptors, is emerging as a promising solution. In the SURMOUNT and SURPASS clinical trials, tirzepatide was shown to effectively reduce body weight and improve metabolic parameters in diabetic and non-diabetic patients, surpassing other available therapies, such as semaglutide in terms of efficacy. Tirzepatide not only promotes weight loss but also helps maintain the effects achieved and reduces cardiovascular risk, making it an important tool in the treatment of obesity. Its clinical benefits are further enhanced by the introduction of intensive lifestyle interventions before starting therapy. In summary, tirzepatide is an innovative approach to the treatment of obesity, offering promising long-term effects while maintaining a favorable safety profile.